Application of uniform asymptotics to the connection formulas of the fifth Painlevé equation. Issue 2 (1st February 2016) - Zeng, Zhao-Yun; Zhao, Yu-Qiu
Abstract : We apply the uniform asymptotics method proposed by Bassom et al. to a special Painlevé V equation, and we provide a simpler and more rigorous proof of the connection formulas for a special solution of the equation, which have been established earlier by McCoy and Tang via the isomonodromy and WKB methods.